Targeting proteostatic maintenance and mitochondrial function with phytochemical compounds in models of brain and skeletal muscle aging - Walsh, Maureen Ann, author; Hamilton, Karyn L., advisor; Fling, Brett W., committee member; Moreno, Julie A., committee member; LaRocca, Thomas J., committee member; Santangelo, Kelly S., committee member (Colorado State University. Libraries, 2024)
There is a growing population of older adults (>65+ years) worldwide that is projected to increase in coming decades, presenting both a challenge and an opportunity. Specifically, age is the number one risk factor for chronic diseases like sarcopenia, the loss of muscle mass and function, and neurodegenerative diseases such as Alzheimer's Disease. The twelve hallmarks of aging are a collection of cellular changes that drive the aging process. Two highly interconnected hallmarks of aging that drive the development and progression of sarcopenia and neurodegeneration are loss of proteostasis (protein homeostasis) and mitochondrial dysfunction. While progress has been made in understanding the etiology of chronic diseases, treatments for age-related chronic diseases affecting skeletal muscle and the brain are lacking. One reason for the lack of effective treatments in humans is the absence of preclinical animal models that recapitulate human aging. However, our group previously identified the Hartley guinea pig as a novel model of brain and skeletal muscle aging. We then treated these guinea pigs with a phytochemical compound to delay the onset and/or slow the progression of brain and skeletal muscle aging. Through the experiments in this dissertation, I observed that: 1.) phytochemical compounds, branded as Protandim, can improve mechanisms of proteostasis independent of changes in mitochondrial respiration in muscle precursor cells; 2.) the phytochemical compound, branded as PB125, can improve mechanisms of skeletal muscle proteostasis in the Hartley guinea pig; 3.) PB125 can also decrease neuroinflammation in the Hartley guinea pig; and 4.) despite the lack of declines in hippocampal mitochondrial respiration with age, Hartley guinea pigs exhibit decreased mitochondrial efficiency. Collectively, this dissertation builds on prior work suggesting that the Hartley guinea pig is a valuable model to test preclinical interventions.